A history of British publishing - Feather, John (Routledge, 2006)
"This revised, restructured and thoroughly updated edition of a classic text covers six centuries of publishing in Britain, from before the invention of the printing press to the electronic era." "In this book, John Feather considers not only the publishing industry itself, but also areas affecting and affected by it, from education, politics, technology and law, to religion, custom and class. He traces the history of the publishing of books in Britain, looking at how they were financed, produced and distributed. Moving into the twentieth century he considers the fate of publishers such as Penguin, Macmillan, Faber & Faber and Collins and how they have fared against the onslaught of the great global corporations which dominate the media today." "In this radically reworked second edition, John Feather places Britain, and her book industries, firmly in the international marketplace. With transatlantic competition and co-operation now standard, and with books marketed across the world via internet stores, Feather concludes by asking, how British is British publishing?"--Jacket